Program Evaluation Particularly Responsive Evaluation* - Robert E. Stake (The Evaluation Center at Western Michigan University, 2011)
Originally published as Paper #5, Occasional Paper Series, November 1975. * Paper presented at a conference on "New Trends in Evaluation", Goteborg, Sweden, October, 1973.